Cross Inoculation of Rumen Fluid to Improve Dry Matter Disappearance and Its Effect on Bacterial Composition Using an in vitro Batch Culture Model - McDermott, Katie; Lee, Michael R. F.; McDowall, Kenneth J.; Greathead, Henry M. R. (Frontiers in Microbiology, 2020)
Environmental pressures of ruminant production could be reduced by improving digestive efficiency. Previous in vivo attempts to manipulate the rumen microbial community have largely been unsuccessful probably due to the influencing effect of the host. Using an in vitro consecutive batch culture technique, the aim of this study was to determine whether manipulation was possible once the bacterial community was uncoupled from the host. Two cross inoculation experiments were performed. Rumen fluid was collected at time of slaughter from 11 Holstein-Friesian steers from the same herd for Experiment 1, and in Experiment 2 were collected from 11 Charolais cross steers sired by the same bull and raised on a forage only diet on the same farm from birth. The two fluids that differed most in their in vitro dry matter disappearance (IVDMD; “Good,” “Bad”) were selected for their respective experiment. The fluids were also mixed (1:1, “Mix”) and used to inoculate the model. In Experiment 1, the mixed rumen fluid resulted in an IVDMD midway between that of the two rumen fluids from which it was made for the first 24 h batch culture (34, 29, 20 g per 100 g DM for the Good, Mix, and Bad, respectively, P < 0.001) which was reflected in fermentation parameters recorded. No effect of cross inoculation was seen for Experiment 2, where the Mix performed most similarly to the Bad. In both experiments, IVDMD increased with consecutive culturing as the microbial population adapted to the in vitro conditions and differences between the fluids were lost. The improved performance with each consecutive batch culture was associated with reduced bacterial diversity. Increases in the genus Pseudobutyrivibrio were identified, which may be, at least in part, responsible for the improved digestive efficiency observed, whilst Prevotella declined by 50% over the study period. It is likely that along with host factors, there are individual factors within each community that prevent other microbes from establishing. Whilst we were unable to manipulate the bacterial community, uncoupling the microbiota from the host resulted in changes in the community, becoming less diverse with time, likely due to environmental heterogeneity, and more efficient at digesting DM.